The difference in pediatric blood pressure between middle childhood and late childhood prior to dental treatment - Syaiful Azim, Fitri Anissa Syaimima; Pertiwi, Arlette Suzy Puspa; Wihardja, Rosiliwati (Padjadjaran Journal of Dentistry, 2013)
Every child will go through several stages in his or her life. They are different from each other as they are in the process of development of cognition, physics, emotion, and personality. For many children, a visit to the dentist can raise their anxiety. This anxiousness will lead to stress that influences the cardiovascular function in the body. The purpose of this research was to determine the difference in pediatric blood pressure between middle childhood and late childhood prior to dental treatment. This research was a clinical trial, pure experimental study. The sample consisted of 30 children within the range of 4-12 years old where they were divided into two groups of age; middle childhood (4-7 years old) and late childhood (8-12 years old). The blood pressures were measured before any dental treatment began and the values were recorded. The data were then analyzed using the One-Sample T-Test analysis. The results of blood pressure in middle childhood and late childhood were compared to the average mean values for each age group. It showed that there was a significant difference in the systolic pressure, which was found higher in the middle childhood group compared to the late childhood. From the result can be concluded that there was a difference in the pediatric blood pressure between middle childhood and late childhood prior to dental treatment.